Adaptations of the human placenta to hypoxia: opportunities for interventions in fetal growth restriction. (30th December 2020) - Colson, Arthur; Sonveaux, Pierre; Debiève, Frédéric; Sferruzzi-Perri, Amanda N
Abstract: BACKGROUND: The placenta is the functional interface between the mother and the fetus during pregnancy, and a critical determinant of fetal growth and life-long health. In the first trimester, it develops under a low-oxygen environment, which is essential for the conceptus who has little defense against reactive oxygen species produced during oxidative metabolism. However, failure of invasive trophoblasts to sufficiently remodel uterine arteries toward dilated vessels by the end of the first trimester can lead to reduced/intermittent blood flow, persistent hypoxia and oxidative stress in the placenta with consequences for fetal growth. Fetal growth restriction (FGR) is observed in ∼10% of pregnancies and is frequently seen in association with other pregnancy complications, such as preeclampsia (PE). FGR is one of the main challenges for obstetricians and pediatricians, as smaller fetuses have greater perinatal risks of morbidity and mortality and postnatal risks of neurodevelopmental and cardio-metabolic disorders. OBJECTIVE AND RATIONALE: The aim of this review was to examine the importance of placental responses to changing oxygen environments during abnormal pregnancy in terms of cellular, molecular and functional changes in order to highlight new therapeutic pathways, and to pinpoint approaches aimed at enhancing oxygen supply and/or mitigating oxidative stress in the placenta as a mean of optimizing fetal growth. SEARCH METHODS: An extensive online search of peer-reviewed articles using PubMed was performed with combinations of search terms including pregnancy, placenta, trophoblast, oxygen, hypoxia, high altitude, FGR and PE (last updated in May 2020). OUTCOMES: Trophoblast differentiation and placental establishment are governed by oxygen availability/hypoxia in early pregnancy. The placental response to late gestational hypoxia includes changes in syncytialization, mitochondrial functions, endoplasmic reticulum stress, hormone production, nutrient handling and angiogenic factor secretion. The nature of these changes depends on the extent of hypoxia, with some responses appearing adaptive and others appearing detrimental to the placental support of fetal growth. Emerging approaches that aim to increase placental oxygen supply and/or reduce the impacts of excessive oxidative stress are promising for their potential to prevent/treat FGR. WIDER IMPLICATIONS: There are many risks and challenges of intervening during pregnancy that must be considered. The establishment of human trophoblast stem cell lines and organoids will allow further mechanistic studies of the effects of hypoxia and may lead to advanced screening of drugs for use in pregnancies complicated by placental insufficiency/hypoxia. Since no treatments are currently available, a better understanding of placental adaptations to hypoxia would help to develop therapies or repurpose drugs to optimize placental function and fetal growth, with life-long benefits to human health.